Parental sacrifice as perceived by adolescents among economics foundation students in IIUM - Izaddin, Radin Mohd Akhmal; Izaddin, Radin Mardhiana (International Organization Center of Academic Research, 2017)
Parental sacrifice shares some similarities with family capital, parental investment and parental involvement that it is related to the contributions of parents to their children’s welfare and development. The objective of this study is to obtain information about adolescents’ perception on the parental sacrifice. Researcher also aims to investigate the differences of perception on parental sacrifice among adolescents between gender as well as home location namely urban and rural. Researcher used descriptive research methodology and survey techniques to collect data from Economics foundation students from IIUM Gombak campus. The size of population for this study is 624 adolescents who were from Economics foundation students of IIUM. Researcher chose 124 samples as respondents. The samples for this study are taken from IIUM Foundation students of Economic department in Gombak campus. Data were collected from the survey respondents represented their perceptions regarding the parental sacrifice. The data obtained, were later analyzed using the SPSS (Statistical Package for the Social Science) software. In analyzing the data, researcher used descriptive statistics and an Independent t-test. The current research revealed that most of the students had moderate level of parental sacrifice. There was a statistically significant difference between male and female in their parental sacrifice where female. The result showed that there was no statistically significant difference between students who came from urban as well as rural area in their perception on parental sacrifice.